"Educación", la revista de la Facultad de Ciencias de la educación: una revisión histórica evaluativa - Campos Arenas, Agustín (2011)
The magazine EDUCATION, issue of the School of Education Sciences, is the first formal magazine of UNIFÉ. This article analyses its historie development through an educational evaluation concept . Eight characteristics or criteria are used in arder to show the advances and difficulties throughout 20 years of issuing (1990 - 2010). The magazine EDUCATION has been consolidated as a professional magazine which sees the future with a great optimism.